The role of positive problem-solving style on marital satisfaction in the early years of marriage - Gusti Agung, Saraswati Dewi; Tience Debora Valentina (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2025)
The early years of marriage often involve various adjustment challenges that may lead to conflict; however, research exploring the role of positive problem-solving styles in marital satisfaction remains limited. This study aims to examine the role of positive problem-solving style in marital satisfaction during the early years of marriage. A quantitative approach was conducted, involving 162 individuals who had been married for ≤ 10 years. The instruments used were a marital satisfaction scale based on aspects developed by Fowers & Olson (1993) and a positive problem-solving style scale constructed based on Kurdek's concept of Conflict Resolution Style. Results of a simple regression analysis showed that positive problem-solving significantly contributed to marital satisfaction (p < .001), accounting for 65.4% of the variance. This finding suggests that individuals who employ constructive and cooperative strategies in managing marital conflicts tend to experience higher satisfaction, underscoring the importance of favorable conflict resolution in maintaining a healthy and fulfilling marriage.